An Investigation of Learning Independence, Motivation, and Physics Learning Outcomes among Students of SMKN 3 Soppeng: A Descriptive Correlational Study - Bohari, Afisma; Abdullah, Helmi; Usman, Usman (Jurnal Pembelajaran Fisika, 2024)
Education is essential for developing self-sufficient students who can pursue their academic goals without significantly depending on outside assistance. In the context of teaching physics, where students frequently struggle with motivation and grasping complicated concepts, this element is very important. The purpose of this study is to examine how learning independence and motivation affect the physics learning outcomes of SMK Negeri 3 Soppeng students in the eleventh grade. Saturated sampling was used to choose 11th grade students from the Computer and Network Engineering department for the 2022–2023 academic year. The research uses a descriptive correlational quantitative method. Learning outcome exams in physics and learning independence and motivation questionnaires were used to gather data. Descriptive and inferential statistics, such as multicollinearity, linearity, and normality tests, were used in the data analysis. Although learning independence contributed only 0.0106% to physics learning outcomes, the results showed a positive and significant association (r = 0.103) between learning independence and learning outcomes. This suggests that other factors may also be important. These results emphasize how critical it is for teachers to create plans that increase students' drive and independence in their learning, since this could lead to better learning outcomes for them when it comes to physics. This study also emphasizes how important it is to take into account additional variables that may affect students' learning outcomes.Keywords: Physics learning outcomes, learning independence, learning motivation, correlational studyDOI: http://dx.doi.org/10.23960/jpf.v12.n1.202401